2012
DOI: 10.1038/ismej.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

Marine microalgae attack and feed on metazoans

Abstract: Free-living microalgae from the dinoflagellate genus Karlodinium are known to form massive blooms in eutrophic coastal waters worldwide and are often associated with fish kills. Natural bloom populations, recently shown to consist of the two mixotrophic and toxic species Karlodinium armiger and Karlodinium veneficum have caused fast paralysis and mortality of finfish and copepods in the laboratory, and have been associated with reduced metazooplankton biomass in-situ. Here we show that a strain of K. armiger (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…A number of Karlodinium species have recently been described from Australia (de Salas et al, 2005,2008), but hemolytic karlotoxins were only present in K. veneficum (Mooney et al, 2009). However, immobilization and ingestion of copepods by K. armiger suggests uncharacterized toxins may be present in other species of the Karlodinium genus (Berge et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…A number of Karlodinium species have recently been described from Australia (de Salas et al, 2005,2008), but hemolytic karlotoxins were only present in K. veneficum (Mooney et al, 2009). However, immobilization and ingestion of copepods by K. armiger suggests uncharacterized toxins may be present in other species of the Karlodinium genus (Berge et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…These dinoflagellates are armored with peduncle that helps their attachment to fish organs like gills and fins where ingestion happens gradually. Unfortunately, this can be lethal when toxic microalgae attack speeds up the toxin release upon contact with the ruptured gills [71]. Recent cases of fish killing were documented in Tanjung Kupang, Johor that involved economical loss to 250 fishermen and fish farmers due to Karlodinium australe [53,72].…”
Section: Water Discoloration and Fish Killingsmentioning
confidence: 99%
“…Intriguingly, mixotrophs can sometimes utilize organisms much larger than themselves for their nutrition. Indeed, working together in groups, some dinoflagellates can even attack and consume copepods (Berge et al 2012); while other dinoflagellates have been shown to be detrital feeders using copepod fecal pellets as a food source (Poulsen et al 2011).…”
Section: Assembling the Protist Puzzlementioning
confidence: 99%
“…Indeed, working together in groups, some dinoflagellates can even attack and consume copepods (Berge et al. ); while other dinoflagellates have been shown to be detrital feeders using copepod fecal pellets as a food source (Poulsen et al. ).…”
mentioning
confidence: 99%